2023
DOI: 10.1371/journal.pone.0271505
|View full text |Cite
|
Sign up to set email alerts
|

Mutant-RB1 circulating tumor DNA in the blood of unilateral retinoblastoma patients: What happens during enucleation surgery: A pilot study

Abstract: Cell free DNA (cfDNA) and circulating tumor cell free DNA (ctDNA) from blood (plasma) are increasingly being used in oncology for diagnosis, monitoring response, identifying cancer causing mutations and detecting recurrences. Circulating tumor RB1 DNA (ctDNA) is found in the blood (plasma) of retinoblastoma patients at diagnosis before instituting treatment (naïve). We investigated ctDNA in naïve unilateral patients before enucleation and during enucleation (6 patients/ 8 mutations with specimens collected 5–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The role of ccfDNA in personalized medicine is at the forefront of a rapidly evolving landscape, offering promising prospects for individualized treatment and enhanced patient care. However, this advancement must be navigated with careful consideration of the associated ethical, practical, and accessibility challenges [50]. This broadening of scope signifies a shift towards a more holistic application of ccfDNA in medicine, transcending traditional boundaries and offering a more comprehensive approach to healthcare [53].…”
Section: Ethical and Practical Considerationsmentioning
confidence: 99%
“…The role of ccfDNA in personalized medicine is at the forefront of a rapidly evolving landscape, offering promising prospects for individualized treatment and enhanced patient care. However, this advancement must be navigated with careful consideration of the associated ethical, practical, and accessibility challenges [50]. This broadening of scope signifies a shift towards a more holistic application of ccfDNA in medicine, transcending traditional boundaries and offering a more comprehensive approach to healthcare [53].…”
Section: Ethical and Practical Considerationsmentioning
confidence: 99%
“…Tumor-specific circulating tumor DNA (ctDNA) is commonly detected in the blood (plasma) of newly diagnosed children with retinoblastoma . Correlative studies in enucleated eyes have confirmed that the source of the ctDNA is the tumor in the eye .…”
Section: Introductionmentioning
confidence: 99%
“…umor-specific circulating tumor DNA (ctDNA) is commonly detected in the blood (plasma) of newly diagnosed children with retinoblastoma. [1][2][3] Correlative studies in enucleated eyes have confirmed that the source of the ctDNA is the tumor in the eye. 4 The half-life of this ctDNA is brief; during enucleation, 50% of the measurable ctDNA fraction ( variant allele frequency [VAF]) becomes undetectable in 10 minutes and 90% within 40 minutes of transecting the optic nerve.…”
mentioning
confidence: 99%
See 1 more Smart Citation